2013
DOI: 10.1007/s10461-013-0497-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rapid HIV Home Test Use with Sexual Partners on Subsequent Sexual Behavior Among Men Who have Sex with Men

Abstract: This study explores the sexual behavior 27 men who have sex with men (MSM) who regularly engage in unprotected anal intercourse (UAI), in the context of HIV home test (HT) use with potential sex partners. Participants were given 16 HT kits to use over three months. Among 40 sexual occasions following HIV-negative HT results, there were 25 UAI occasions (16 based on not typically using condoms and nine on HT results), 15 occasions in which condoms were used, and three in which sex did not occur. In the seven oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 27 publications
(21 reference statements)
0
48
1
1
Order By: Relevance
“…Doing so will be his choice. He may also derive a benefit from it; one study analysed the use of HIV self-testing kits in this manner among high-risk MSM, and concluded that it reduced HIV transmission 34. It must always be remembered that the gateway to HIV prevention and effective HIV treatment is testing.…”
Section: Novel Scenariosmentioning
confidence: 99%
“…Doing so will be his choice. He may also derive a benefit from it; one study analysed the use of HIV self-testing kits in this manner among high-risk MSM, and concluded that it reduced HIV transmission 34. It must always be remembered that the gateway to HIV prevention and effective HIV treatment is testing.…”
Section: Novel Scenariosmentioning
confidence: 99%
“…With access to self-testing kits, over 50% reported a change in their attitudes and/or behaviors, including a greater awareness of risk and more discussion of safe sex practices with partners 38. Participants also reported a change in choice of partners and in seven instances when a potential partner tested positive by a rapid HIV test kit, the sexual encounter stopped; more than one-half of the participants also ended sexual encounters when an HIV rapid test was refused by a sex partner 39. No sexual intercourse took place after a positive test, indicating that “point-of-sex” testing can lead to increased awareness of risk and can avert sex between discordant partners 40.…”
Section: Arguments For Hiv Self-testing: Accessibility; Accuracy; Empmentioning
confidence: 99%
“…The home HIV test -now licensed in the USA and the UK -is maybe the apotheosis of this productive, but perhaps troubling, mix of biomedical authority and sexaffirmative politics. Researchers have provided gay men in NYC with rapid home testing kits (Balan et al 2014) and asked them to report back on how they used the technology to make decisions regarding anal sex and condoms. Findings suggest that the technology is used to sero-sort out of sexual encounters -with or without condoms -gay men with HIV, among other effects.…”
Section: From Managed Consumerism To the Clinic Without Wallsmentioning
confidence: 99%